Exercise Training at Maximal Fat Oxidation Intensity for Older Women with Type 2 Diabetes - Tan, Sijie; Du, Ping; Zhao, Wanting; Pang, Jiaqi; Wang, Jianxiong (International Journal of Sports Medicine, 2018)
The purpose of this study was to investigate the pleiotropic effects of 12 weeks of supervised exercise training at maximal fat oxidation (FATmax) intensity on body composition, lipid profile, glycemic control, insulin sensitivity and serum adipokine levels in older women with type 2 diabetes. Thirty-one women with type 2 diabetes, aged 60 to 69 years, were randomly allocated into exercise and control groups. Body composition, lipid profile, blood glucose, insulin resistance and serum leptin and adiponectin concentrations were measured before and after the intervention. Exercise group (n=16) walked at individualized FATmax intensities for 1 h/day for 3 days/week over 12 weeks. No dietary intervention was introduced during the experimental period. Maximal fat oxidation rate was 0.37±0.10 g/min, and occurred at 37.3±7.3% of the estimated VO2max. Within the exercise group, significant improvements were observed for most of the measured variables compared to non-exercising controls; in particular, the FATmax program reduced body fat% (p<0.001), visceral fat% (p<0.001), and insulin resistance (p<0.001). There was no significant change in daily energy intake for all participants during the intervention period. These results suggest that individualized FATmax training is an effective exercise training intensity for managing type 2 diabetes in older women.
Keywords: type 2 diabetes; exercise training; maximal fat oxidation rate; adipokine